Optimization of Injection molding Parameters using the Taguchi Method to Maximize Biocomposite Material Tensile Strength - Sufiyanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2017)
This research explained a study for optimization of parameters process on the injection molding biocomposite material, which is a mixture of plastics and natural fibers. Natural fibers used is rice husk (RH) mixed with polypropylene (PP) and maleic anhydride polypropylene (MAPP). The biocomposite molded into tensile specimens ASTM D638-03 using the injection molding machine. The varied of injection molding is the parameters process, that are divided into 4 parameters and each consists of 3 levels, then be done tensile tests on specimens. Optimization performed using the Taguchi method with orthogonal matrix design L27(313). The maximum tensile strength of biocomposite were barrel temperature of 210°C, injection pressure of 55 bar, holding pressure of 40 bar, and injection velocity of 75 mm/sec.